Case Report: Dramatic response to entritinib in a patient with gastrointestinal stromal tumor positive for NTRK3 fusion - Dong, Guomin; Han, Pengyu; Zhang, Zhiyun; Ge, Qian; Jiang, Jian; Li, Suoni; Ma, Jiequn; Bai, Jie; Wei, Hui; Zhao, Zheng (Frontiers in Oncology, 2025)
Gastrointestinal stromal tumors (GISTs) are the most common mesenchymal tumors of the gastrointestinal tract, with proto-oncogene, receptor tyrosine kinase (c-kit), or PDGFRα mutations detected in around 85% of cases. GISTs without c-kit or platelet-derived growth factor receptor alpha (PDGFRα) mutations are considered wild-type (WT). Recently, some molecular alterations, including neurotrophic tyrosine receptor kinase (NTRK) fusions, have been reported in very few cases of WT GISTs. This novel finding opens the window for the use of tropomyosin receptor kinase (TRK) inhibitor therapy in these subtypes of GIST. In this case report, we present a rare NTRK3 fusion gastrointestinal stromal tumor (GIST) in a female patient with significant response to entrectinib. The patient was initially diagnosed with a giant gastric GIST (approximately 20.6cm×12.1cm×28.0m in size) showing classic immunohistochemical features (CD117+/DOG1+) on immunohistochemistry. After neoadjuvant imatinib therapy (400 mg/day), partial response was achieved with tumor shrinkage to 14.1cm×7.6cm×15.5cm, followed by radical surgery. Postoperative pathology confirmed high-risk GIST (ypT4N0), with genetic testing revealing a KIT exon11 deletion mutation (p.K558_V560del, VAF 63.80%). Continued oral imatinib adjuvant therapy was initiated. In 2024, disease progression was observed with residual KIT mutation (VAF 1.10%) and new-onset ETV6:NTRK3 fusion (VAF 35.29%) detected by circulating tumor DNA (ctDNA) analysis. Switching to entrectinib (600 mg/day) achieved partial imaging response within 4 weeks (tumor reduction of approximately 27%), with complete clearance of dual mutations observed in ctDNA after 3 months. The patient maintained sustained response without adverse events during final follow-up. This case highlights the breakthrough efficacy of TRK inhibitors in treating NTRK-fusion GIST and confirms the critical value of liquid biopsy in monitoring drug resistance mechanisms and guiding precision treatment.